(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This paper investigates the connection between ethnophilosophy and indigenous knowledge systems, exploring how these approaches can enhance contemporary philosophical thought. Ethnophilosophy serves as a method to deeply engage with the philosophical ideas found in the worldviews of indigenous communities, challenging the dominance of Western knowledge systems and bringing to light alternative perspectives that emphasise relationships, interconnectedness, and the importance of context. By integrating these indigenous perspectives, the paper argues for a more inclusive and diverse understanding of philosophy. The study also examines the ethical and metaphysical insights offered by indigenous knowledge systems, particularly their emphasis on the interconnectedness of all life and the sacredness of the natural world. These ideas offer a contrast to the more human-centred views often found in Western philosophy, suggesting a broader ethical framework that includes all living beings. Additionally, the paper explores the role of ethnophilosophy in the process of decolonising knowledge, proposing that recognising and valuing indigenous thought can lead to more equitable and sustainable practices around the world. In essence, this paper advocates for a philosophical approach that is inclusive of diverse intellectual traditions, asserting that the insights from indigenous knowledge systems are not just relevant but vital in addressing the complex challenges we face today.